Evaluation of Salivary Biomarkers in the Early Detection of Oral Squamous Cell Carcinoma - Ibrahim A. AlZoubi; Mohammad Khursheed Alam; Reef Bashar Saad Alkayid; Haya Okab Alruwaili; Ethar Oqab Alruwaili; Taif Abdulaziz Alsaleh; Fawaz Talal F Alanazi; Nor Farid Bin Mohd Noor (Journal of Pharmacy and Bioallied Sciences)
Background: The most prevalent cancer of the oral cavity is oral squamous cell carcinoma (OSCC), which often presents at an advanced stage with a poor prognosis and high death rates. As non-invasive diagnostic methods, salivary biomarkers have shown promise in the early diagnosis of OSCC. The purpose of this research is to assess certain salivary biomarkers to ascertain how well they can detect OSCC in its early phases. Materials and Methods: Ninety participants were split into three groups for a cross-sectional study: 30 OSCC patients, 30 people with oral premalignant lesions (OPLs), and 30 healthy controls. The enzyme-linked immunosorbent assay was used to measure the levels of interleukin-6 (IL-6), matrix metalloproteinase-9 (MMP-9), and lactate dehydrogenase (LDH) in unstimulated saliva samples. ANOVA and post-hoc Tukey tests were used in the statistical analysis to compare the amounts of biomarkers in each group. Results: OSCC patients had a mean IL-6 concentration of 250 ± 25 pg/mL, which was substantially greater than the OPL group’s concentration of 100 ± 15 pg/mL and the healthy controls’ concentration of 30 ± 5 pg/mL (P < 0.001). Similarly, OSCC patients had higher MMP-9 levels (500 ± 50 ng/mL) than OPL (300 ± 40 ng/mL) and controls (100 ± 20 ng/mL) (P < 0.001). The OPL group (600 ± 60 U/L) and controls (300 ± 50 U/L) had lower LDH activity than OSCC patients (850 ± 70 U/L) (P < 0.001). High sensitivity and specificity were shown by receiver operating characteristic curve analysis for all three biomarkers in differentiating OSCC from OPL and healthy controls. Conclusion: Salivary biomarkers, including MMP-9, LDH, and IL-6, show great promise for the early, non-invasive identification of OSCC. By integrating these biomarkers into standard diagnostic procedures, OSCC-related morbidity and mortality may be decreased and early diagnosis and treatment results may be enhanced.